Comparing wood production and carbon sequestration after extreme thinnings in boreal Scots pine stands - Bianchi, Simone; Huuskonen, Saija; Hynynen, Jari; Niemistö, Pentti (Forest Ecology and Management)
Fennoscandian studies of thinning responses are usually limited to low thinning with moderate intensities. We studied here intermediate commercial thinning of different types (low, crown/normal, crown/strict, where respectively mostly intermediate and suppressed trees, mostly dominant and co-dominant trees, and only dominant trees were removed) and intensities (moderate and heavy) in Scots pine (Pinus sylvestris L.) dominated stands. We analysed their responses in terms of wood production and carbon balance. We investigated three stands in Southern and Middle Finland at the stage of second or third commercial thinning (age 34–50 years). We observed their development for fifteen years, and then we further simulated it with MOTTI stand simulator until final felling (scheduled either at age 65 or 80 years). We considered various variables of interest related to the thinning outputs, volume production after thinning, simulated final felling, and carbon balance. For all variables of interest, there were negligible differences across thinning types, and strong ones across thinning intensities. Thinning removals were significantly higher in heavy than moderate treatments, although only crown heavy thinnings had significantly higher sawlog output than low moderate. Volume growth post thinning during the 15-years observation was highest in unthinned plots, followed by moderate and then heavy treatments. For both total standing volume at simulated final fellings and carbon balance at any times, there was a similar descending trend from unthinned to moderate to heavy treatments. Concluding, the results suggest that crown/normal thinning could be applied with moderate intensity as alternative to low thinning, while heavy thinnings do not provide commercial benefits in Scots pine stands. Heavy intermediate thinnings in Scots pine stands provides lower total carbon accumulation during rotation, and early higher wood products (although not necessarily in terms of sawlogs) at the expense of later ones. Moderate thinning reached ...